Putting population and global health on the agenda of health professionals - Robyn Woodward-Kron (SAGE Publishing, 2016)
Health professional education curricula are notoriously contested and constrained. Diverse epistemological and pedagogical objectives compete for space amid complex schedules of clinical placements, rotations, laboratory work, lectures, and other core curriculum activities. Health professional educators must navigate these constraints as well as address course accreditation standards and the expectations and needs of their communities. Accreditation standards for health professional courses are designed to ensure that graduates are competent to practise safely and effectively; they are also designed to ensure graduates can address health issues in the broader community and populations. Health professional education and training should therefore provide understandings of environmental and social determinants of health and disease still contributing to systemic health inequalities; it should help health professionals appreciate the health and wellbeing needs of indigenous peoples and the social and historical contexts of these health needs. [...]